The Deterioration Mechanism of Diester Aero Lubricating Oil at High Temperature - Ting Yao; Hongwei Yang; Li Guo; Yiwei Fei; Huize Jiang; Sen Bian; Tonghai Wu (Journal of Spectroscopy)
The deterioration of aero lubricating oil at high temperatures was accelerated by using a specific device simulating the operating conditions of engines, where the deterioration mechanism was obtained. Structures of the deteriorated lubricating oils were analyzed by gas chromatograph/mass spectrometer. From the results, it can be concluded that deterioration of aero lubricating oil at high temperatures was composed of thermal pyrolysis, oxidation, and polymerization, with the generation of a variety of products, such as alcohols, aldehydes, acids, and esters, which caused the deterioration of physicochemical properties of the aero lubricating oil.